2009
DOI: 10.1002/hipo.20658
|View full text |Cite
|
Sign up to set email alerts
|

Wheel running and environmental enrichment differentially modify exon‐specific BDNF expression in the hippocampus of wild‐type and pre‐motor symptomatic male and female Huntington's disease mice

Abstract: Brain-derived neurotrophic factor (BDNF) is an essential neurotrophin and regulation of its expression is complex due to multiple 5' untranslated exons which are separately spliced to a common coding exon to form unique mRNA transcripts. Disruption of BDNF gene expression is a key to the development of symptoms in Huntington's disease (HD), a fatal neurodegenerative condition. Abnormal epigenetic modifications are associated with reduced gene expression in late-stage HD but such regulation of BDNF gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
123
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 86 publications
(112 reference statements)
9
123
2
6
Order By: Relevance
“…The paradigm of environmental enrichment employs increased mental, physical and social stimulation in animal models to enhance neurological input, thereby modulating brain activity and physical parameters to impact on disease progression [62][63][64][65][66][67] . A number of studies have shown the benefits of such an approach in Huntington's disease transgenic animal models, with evidence for it being able to delay the onset of motor abnormalities, slow disease progression, reduce impairments to weight loss, balance and physiological factors, and increase both neurogenesis and CNS levels of neurotransmitter receptors, neurotrophins and factors related to synaptic signal transduction pathways [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] .…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The paradigm of environmental enrichment employs increased mental, physical and social stimulation in animal models to enhance neurological input, thereby modulating brain activity and physical parameters to impact on disease progression [62][63][64][65][66][67] . A number of studies have shown the benefits of such an approach in Huntington's disease transgenic animal models, with evidence for it being able to delay the onset of motor abnormalities, slow disease progression, reduce impairments to weight loss, balance and physiological factors, and increase both neurogenesis and CNS levels of neurotransmitter receptors, neurotrophins and factors related to synaptic signal transduction pathways [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] .…”
Section: List Of Figuresmentioning
confidence: 99%
“…Exercise induces increased BDNF expression in rodents 104,105 and in human populations [106][107][108] and cortical expression is upregulated in animal models, including models of Huntington's disease, after exercise or environmental enrichment 77,82,109,110 .…”
Section: D-kefs Trail Makingmentioning
confidence: 99%
“…Rodents with anhedonia, as can be induced by long-term impoverished caging [26] and also varies with strain [27] with enrichments that to other rodents act as valued incentives. Overall, variation between rodents in neophobia and anhedonia may thus help explain why not just strain, but also sex, age and individual characteristics can influence experimental outcomes, even when enrichments are carefully standardized [28][29][30][31][32][33][34][35]. Here, we therefore used individual variation in responses to standardized enrichments to conduct preliminary tests of the hypotheses that neophobia and anhedonia affect the extent to which mice interact with environmental enrichments.…”
Section: Introductionmentioning
confidence: 99%
“…Changes to the enrichments and cage layout occurred weekly at cage cleaning, following the protocols of prior studies [35,39,40]; on this day, mice were denied access to the enriched cage. Enriched cages were always re-provisioned in the same way so that all 19 remained identical.…”
Section: Introductionmentioning
confidence: 99%
“…Rodents with anhedonia, as can be induced by long-term impoverished caging [26] and also varies with strain [27] may also fail to show much interaction with enrichments that to other rodents act as valued incentives. Overall, variation between rodents in neophobia and anhedonia may thus help explain why not just strain, but also sex, age and individual characteristics can influence experimental outcomes, even when enrichments are carefully standardized [28][29][30][31][32][33][34][35]. Here, we therefore used individual variation in responses to standardized enrichments to conduct preliminary tests of the hypotheses that neophobia and anhedonia affect the extent to which mice interact with environmental enrichments.…”
mentioning
confidence: 99%